System of modern business communication as a subject of research - Shavkun, Iryna; Dybchynska, Yana (Management and Entrepreneurship: Trends of Development, 2025)
The purpose of this study is a comprehensive analysis of business communication as an integrated system, identifying the key stages in the evolution of its strategies, as well as analyzing modern challenges caused by digital, social and institutional transformations in order to determine the directions for further development of effective communication practices in the business environment. Research objectives are: to reveal the theoretical foundations of business communication as a systemic phenomenon, to identify its structural elements and principles of operation; to analyze the stages of evolution of business communication strategies in the context of historical, technological and social changes.; to characterize the modern challenges that organizations face when building effective communication systems (including digitalization, information overload, audience fragmentation, growing importance of reputational capital etc.). The comprehensive and systemic approaches allows to deeply investigate modern business communication as a system, with particular attention to strategy development and emerging challenges. The main attention is paid to the analysis of the evolution of business communication strategies, the transformation of tools and the problems of the communication process in organizations operating in an information-saturated environment. The results can be useful for specialists in corporate communications, PR and strategic management in developing and adapting communication strategies taking into account new challenges ‒ digitalization, audience fragmentation, the growing importance of reputational capital and crisis preparedness. JEL Classification: L 14, D83, M1, M 12, B4